2022
DOI: 10.3390/agriculture12030356
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Zeolite from Coal Fly Ash on Soil Hydrophysical Properties and Plant Growth

Abstract: Zeolites can be extensively employed in agricultural activities because they improve soil properties such as infiltration rates, saturated hydraulic conductivity, water holding capacity, and cation exchange capacity. Natural and synthetic zeolites can efficiently hold water. Zeolites are also believed to have the ability to lose and gain water reversibly, without changing their crystal structure. In the present study, several laboratory tests were carried out using: (i) zeolite synthesized from coal fly ash (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…An increase in specific surface area and a decrease in pore size can result in, among other things, reduced oxygen diffusion, mineralization of humic compounds, and loss of organic carbon stocks. This phenomenon is particularly beneficial in soils with low organic matter content and relatively poor aeration [ 94 ]. Zeolite incorporation can also improve nutrient retention [ 14 ] and help buffer soil pH, reducing the need for lime [ 28 ].…”
Section: Applications Of Zeolitesmentioning
confidence: 99%
“…An increase in specific surface area and a decrease in pore size can result in, among other things, reduced oxygen diffusion, mineralization of humic compounds, and loss of organic carbon stocks. This phenomenon is particularly beneficial in soils with low organic matter content and relatively poor aeration [ 94 ]. Zeolite incorporation can also improve nutrient retention [ 14 ] and help buffer soil pH, reducing the need for lime [ 28 ].…”
Section: Applications Of Zeolitesmentioning
confidence: 99%
“…On the other hand, BC significantly affected the GP and potential due to its high porosity and large specific surface area, improving soil water retention and air permeability [29][30][31]. While ZL may have limited direct effects on plant height and coverage rate, the enhanced soil conditions indirectly promote plant growth and vegetation coverage by facilitating root expansion and nutrient absorption [32,33]. Conversely, BC has a more direct impact on plant height, as its improved water retention and nutrient environment directly influence plant growth rate and health, aligning with Kang et al's [34] findings.…”
Section: Two-factor Variance Analysis Of Vegetative Propertiesmentioning
confidence: 99%
“…The results indicated that zeolite addition increases the water retention capacity of soil and decreases the drainage capacity. The treatments with high concentrations of synthetic zeolite (5% and 10%) drastically reduce sunflower growth while a concentration of zeolite between 1 and 2% caused a slight decrease in growth (Belviso et al., 2022).…”
Section: Application Of Zeolites From Residues In Plant Growthmentioning
confidence: 99%